Distance Education Is A Bet And A Challenge To The Development Of The Library And Information Profession - Elhebouchi , fatiha; Aboura Nadji , Yamina (Journal of Social Sciences and Humanities, 2021)
This work aims to highlight the importance of distance education in the field of library and information science and its importance to the development of the library profession and to revitalize it in the field in a more modern and sophisticated way. The various changes and transformations that the profession and specialization have witnessed in the world as a whole have imposed on librarians the skills and competencies that enable them to face these challenges and stakes in the field and give it a distinctive elegance. Education and training in libraries and information centers on a permanent and continuous basis as a result of these transformations has become more than a necessity for the quality of the services provided, which aim to promote the scientific and intellectual production of the beneficiaries, especially in the field of scientific and academic research. This research paper aims to address the issue of training and distance education as a strategy for developing the library and information profession in general and in Algeria in particular.